The first signs of grammar lessons in the MaghrebAl Mokadimma El jazoulia as Model (مجلة إحالات, 2026)
The recent study deals with one of the earlier and great arab reaserchers in Arab Maghreb, who is Abu Musa al-Jazouli. We want in that study to define his great work wich called « Al –Mokadima Al-jazoulia (Introduction to Grammar) to expose his contribution and effort with critics,comparison and annalysis.to state at the end of this work that Abu Musa al-Jazouli is one of thegreatest arab grammarian in arab maghreb as the grammarians of the Arab Orient.